USE OF MANAGEMENT INFORMATION SYSTEMS TO IMPROVE THE EFFECTIVENESS OF HUMAN RESOURCE MANAGEMENT - Ira Wahyuni; Athaya Hargita; Rayyan Firdaus (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Efficient human resource management is a key element in enhancing institutional competitiveness. In today's digital era, the implementation of Management Information Systems (MIS) has become crucial for institutions to manage various aspects of HR, including recruitment, capability development, performance evaluation, and administrative management. This study aims to investigate how the implementation of MIS can improve the effectiveness of HR management, particularly in the context of modern organizations. Through a literature review of various relevant Indonesian journals, the study findings reveal that the implementation of MIS can provide clarity, efficiency, and accuracy of data that supports managerial decision-making related to HR. In addition, MIS also encourages collaboration between divisions, facilitates direct data access, and supports talent development strategies in a more planned manner.